UJI IN SILICO SENYAWA EMODIN SEBAGAI LIGAN PADA RESEPTOR ESTROGEN ALFA - Liliana Liliana; Enade Perdana Istyastono (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2015)
Breast cancer is a disease with abnormal cell proliferation at breast tissue that can invade the surrounding tissue and spread to another organ. Based on WHO (2014) at 2012, there are 48,998 breast cancer cases on women in Indonesia with 19,730 death cases. In breast cancer, overexpression estrogen receptor alpha (ER-?) usually observed. Hence ER-? became the focus of prevention and therapy for breast cancer. In vitro study of emodin shows IC50 2.7 M and Ki 0.77 M on ER-?. In silico research using docking protocol and post docking analysis protocol shown that emodin was not an active ligand on ER-?. The outcome shown as ChemPLP score with average -75.292 and PLIF bitstring. Emodin binds with LEU346, LEU387, and ARG394 residue. Currently, the protocol that used in this research has yet identified marginal compound like emodin as an active ligand on ER-?.